PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN DI PERGURUAN TINGGI KOTA BALIKPAPAN - Eltimeyansi Crisye Randanan; Esterina Natalia Paindan; Risna Risna (PETROGAS: Journal of Energy and Technology, 2019)
Management of hazardous and toxic waste is one of the most important things in handling waste for better nature. Good management can result in a clean water, air and soil environment, good quality of human life and a balanced human future.